Islam under siege - "Ahmed, Akbar S" (New Delhi, 2003)
In this groundbreaking book, Akbar Ahmed, one of the world's leading authorities on Islam, who has worked in the Muslim world but lives in the West, explains what is going wrong in his society by referring to Islamic history and beliefs. Employing theological and anthropological perspectives, he attempts to answer the questions that people in the West are asking about Islam: "Why do they hate us?" "Is Islam compatible with democracy?" "Does Islam subjugate women?" "Does the Quran preach violence?" These important questions are of relevance to Muslims and to non-Muslims alike. Islam Under Siege points out the need for, and provides the route to, the dialogue of civilizations.
Keywords: Muslims